METHODS AND COMPLICATIONS OF SEPTIC INDUCED ABORTION IN PATIENTS MANAGED AT A TERTIARY CARE HOSPITAL - Jabeen, Alia; Dawood, Nasira Sabiha; Riaz, Shazia; Tanveer, Shamaila (Journal of Ayub Medical College Abbottabad, 2013)
Background: To study the methods used for the termination of pregnancy and associated complications of induced abortion. Methods: This descriptive study was conducted in the department of obstetrics and gynaecology, Fauji Foundation Hospital Rawalpindi. One Hundred patients were included in the study who was admitted with the history of induced abortion. The patients were assessed by detailed history and thorough clinical examination according to the study protocol. Data was collected on a specially designed Performa. Patients were interviewed in privacy and factors contributing to termination of pregnancy like age, parity, socioeconomic status and contraceptive failure were determined. Methods used for the procedure, status of abortionist were asked. Complications were determined by history, clinical examination and ultrasound examination. In view of all above data recommendations of preventing unwanted pregnancies were made. Results: All patients were married and 57% of women belonged to age group of 31-40 years. Fifty-four 54% were grand multipara. In 63% of patients, induced abortion was carried out by Dai's. Most commonly used method was instrumentation (72%). Financial problems (46.7%) and high parity (40%) were the most common factors contributing to termination of pregnancy. Serious complications like uterine perforation with or without bowel injury were accounted in 13% of women, septicaemia in 61%, peritonitis in 15% and DIC in 2%. During the study period illegally induced abortion accounted for 2% maternal deaths. Conclusion: Prevalence of poverty, illiteracy, grand multiparity and non-compliance of contraception were strong determinants of induced abortion, instrumentation being the most commonly used procedure resulting in high morbidity and mortality. Keywords: Abortion, complications, Induced abortion, Morbidity, mortality, Uterine perforation, Septicaemia, DIC